Assessing subaortic right ventricle function after atrial switch repair through myocardial work analysis - Ana Moya; Sofie Verstreken; Dimitri Buytaert; Monika Beles; Elayne Kelen de Oliveira; Marc Vanderheyden; Alexander Van De Bruaene; Werner Budts (International Journal of Cardiology Congenital Heart Disease)
Background: The Mustard and Senning operations for dextro-transposition of the great arteries (D-TGA) establish a biventricular physiology with a subaortic right ventricle (sRV). While prolonged QRS has been associated with worse prognosis in these patients, current echocardiographic tools fall short in adequately assessing the (mal)performance and function decline of the sRV during follow-up. The present study is the first to characterize Myocardial Work (MW) indices of the sRV in D-TGA patients after Mustard/Senning repair. Methods and results: All adult D-TGA patients at follow-up in the University Hospital of Leuven between 2018 and 2022 were screened for inclusion. We retrospectively collected the most recent electrocardiogram parameters, 2D echocardiographic images and serum biomarkers’ values. Offline calculations of MW indices were performed. We established correlations between all variables and categorized patients into QRS<120 ms and QRS≥120 ms for further analysis. A total of 51 D-TGA patients were included (13 Mustard, 33 male, 39 ± 6 years). QRS duration increased with age and was correlated with sRV dimensions and serum levels of troponins (R = 0.42, p < 0.01) and NT-proBNP (R = 0.31, p = 0.03). However, no significant correlation was found between QRS duration and intraventricular desynchrony or conventional functional echocardiographic parameters. QRS prolongation was associated with a deterioration in septal, but not lateral, MW parameters. Patients with QRS≥120 ms had significantly larger ventricles and higher levels of troponins and NT-proBNP. Conclusion: QRS prolongation after Mustard/Senning repair is linked to ventricular dilatation and worse performance, particularly affecting the septal wall. Global and regional MW analysis may be useful to assess the subclinical deterioration of sRV function.